1988
DOI: 10.1159/000146614
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Growth in Apert Syndrome as Measured by Finite-Element Scaling Analysis

Abstract: A new tool for the study of biological form change is applied in a comparison of craniofacial growth in normal children and those affected with Apert syndrome. Using finite-element scaling analysis, the magnitude of size change during postnatal growth in the Apert sample was determined to be generally less than normal, and the magnitude of shape change was generally greater than normal. No consistent, statistically significant, alteration from normal growth was defined in the Apert sample, however. There appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 5 publications
(6 reference statements)
1
11
0
Order By: Relevance
“…Accordingly, Kohn et al (1993) showed that annular deformations of the cranial vault produce significant effects on the morphology of the cranial base and face. Similar conclusions arise from experimental vault deformation in mice (Pucciarelli 1978), and studies of premature closure of cranial sutures (Babler et al 1987), and craniosynostoses (Moss 1959;Kreiborg 1981;Richtsmeier 1987Richtsmeier , 1988Richtsmeier , 2002. Even when these previous studies focused on absolute morphological differences rather than on covariances among traits, their results are useful to evaluate and compare the degree of localization of the effect of biomechanical different ACD types.…”
Section: Developmental Constraintsmentioning
confidence: 60%
“…Accordingly, Kohn et al (1993) showed that annular deformations of the cranial vault produce significant effects on the morphology of the cranial base and face. Similar conclusions arise from experimental vault deformation in mice (Pucciarelli 1978), and studies of premature closure of cranial sutures (Babler et al 1987), and craniosynostoses (Moss 1959;Kreiborg 1981;Richtsmeier 1987Richtsmeier , 1988Richtsmeier , 2002. Even when these previous studies focused on absolute morphological differences rather than on covariances among traits, their results are useful to evaluate and compare the degree of localization of the effect of biomechanical different ACD types.…”
Section: Developmental Constraintsmentioning
confidence: 60%
“…The data are examined lon-within each sample: normal, Crouzon, and gitudinally in alternate studies (Richtsmeier, Apert. One by one, within each age class, the ,1987Richtsmeier and Cheverud, 1986). age-specific standard (normal mean) is deReaders interested in the composition of the formed into each of the normal individuals three samples by individual and age group which combine to make the mean.…”
Section: Datamentioning
confidence: 99%
“…The mode of statistical analysis applied here is a single example of the possible ways in which to test hypotheses about morphological differences between groups of forms. Alternate quantities and methods have been used to summarize form change calculated by finite element and other related methods (Moss et al, 1985(Moss et al, , 1987Cheverud and Richtsmeier, 1986;Richtsmeier and Cheverud, 1986;Lavelle, 1985;Grayson et al, 1985;Richtsmeier, 1987). Experience will determine the values and methods which are most appropriate to specific research problems.…”
Section: No Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not a specific pattern of malgrowth is the process responsible for this age progressivity in dysmorphology has not been sufficiently determined (but see Kreiborg, 1986;Richtsmeier, 1988).…”
Section: Example 2: Dysmorphology In Apert Syndromementioning
confidence: 99%